Isolating membrane, battery monomer, battery and electric device

CN119744476AActive Publication Date: 2025-04-01CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380060936.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-04-01
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The cycle performance of existing battery cells is poor, and the increased gap between pole pieces leads to a high risk of liquid shortage and bridge breakage, which affects battery life.

Method used

An isolation membrane is used, including a polymer layer. The polymer layer is composed of a liquid-retaining polymer and an adhesive polymer. A three-dimensional connection network is formed through the stretching of the polymer molecular chain and the diffusion of the electrolyte to enhance the adhesion between the pole piece and the isolation membrane. properties and stability, and improve the ion transport interface.

Benefits of technology

It improves the cycle performance of the battery cells, reduces the risk of increased spacing caused by the expansion of the pole pieces, improves the electrolyte content and active ion transmission efficiency of the electrode assembly, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744476A_ABST
    Figure CN119744476A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane, a battery monomer, a battery and a power utilization device, the isolating membrane comprises an isolating body and a polymer layer arranged on at least one surface of the isolating body, the polymer layer comprises a liquid-retaining polymer, and the liquid-retaining polymer is added into a first solvent at 70 DEG C to form a polymer system; the polymer system is stood for 8 hours at 70 DEG C, after the polymer system is stood for more than or equal to 24 hours at 25 DEG C, the polymer system is filtered by a 200-mesh filter screen to obtain a first substance, the mass of the liquid retaining polymer is q, and the unit of the liquid retaining polymer is g; the mass of the first substance is m, and the unit of the first substance is g; the liquid retaining polymer and the first substance meet the following conditions: m / q is more than or equal to 5 and less than or equal to 1000; and the binding power of the isolating membrane is greater than or equal to 10N / m.
Need to check novelty before this filing date? Find Prior Art

Description

Separator, battery cell, battery and electrical device Technical Field

[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, a battery cell, a battery, and an electrical device. Background Art

[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.

[0003] As battery applications become increasingly widespread, the requirements for battery cell performance are becoming increasingly stringent. However, the current cycle performance of battery cells is relatively poor and still needs to be further improved.

[0004] Summary of the Invention

[0005] The embodiments of the present application are made in view of the above-mentioned problems, and an object thereof is to provide a separator, a battery cell, a battery, and an electric device.

[0006] The first aspect of the present application provides an isolation membrane, which includes an isolation body and a polymer layer arranged on at least one surface of the isolation body, the polymer layer includes a liquid-retaining polymer, and the isolation membrane includes an isolation body and a polymer layer arranged on at least one surface of the isolation body, wherein the liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; after the polymer system is allowed to stand for 8 hours at 70°C and for ≥24 hours at 25°C, the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the liquid-retaining polymer is q, and its unit is g; the mass of the first substance is m, and its unit is g; the liquid-retaining polymer and the first substance satisfy: 5≤m / q≤1000; and the bonding force of the isolation membrane is greater than or equal to 10N / m.

[0007] Thus, the separator of the embodiment of the present application includes a polymer layer, the polymer layer includes a liquid-retaining polymer, and the separator has excellent bonding properties, so that the separator and the electrode are tightly bonded, thereby alleviating the lack of liquid caused by the increase in the gap between the electrode pieces during the battery cycle, and improving the cycle performance of the battery cell. On the other hand, the liquid-retaining polymer is arranged on the surface of the separator, and the liquid-retaining polymer contacts the electrolyte. The polymer molecular chains stretch and open, and the electrolyte can diffuse between the molecular chains. The polymer molecular chains swell and adsorb, and form a three-dimensional connection network between the separator and the electrode piece. The three-dimensional connection network can adhere to the surface of the electrode piece, bonding the separator and the electrode piece into one, further improving the stability of the electrode piece and diaphragm structure, and improving the cycle performance of the battery cell. In addition, the three-dimensional connection network can lock the electrolyte within the three-dimensional connection network, so that the electrolyte can be maintained in the electrode piece and diaphragm structure, which is beneficial to improving the ion transmission interface and facilitating the transmission of active ions such as lithium ions and sodium ions, and can further improve the cycle performance of the battery cell.

[0008] In some embodiments, the separator has an adhesive force of 10 N / m to 30 N / m. When the separator has an adhesive force within the above range, the separator has good adhesion, which helps improve the connection stability between the separator and the electrode. This reduces the risk of increasing the distance between the separator and the electrode during the charge and discharge cycle of the battery cell, thereby allowing the electrode assembly to absorb a larger amount of electrolyte, which helps improve cycle performance.

[0009] In some embodiments, the polymer layer includes an adhesive polymer, and the adhesive polymer includes one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and polyethyl acetate (VAE emulsion). The above adhesive polymers have good adhesive properties.

[0010] Further optionally, the polyacrylates include polyethyl acrylate.

[0011] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer is (1 to 9):1. When the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer is within this range, both the adhesion and gel properties of the polymer layer can be improved.

[0012] In some embodiments, the liquid-retaining polymer comprises a fluoropolymer; the crystallinity of the fluoropolymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.

[0013] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.

[0014] In some embodiments, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),

[0015] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom;

[0016] In formula (AIII),

[0017] R 15 including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is a positive integer selected from 1 to 3; and n is a positive integer selected from 1,000 to 30,000.

[0018] In some embodiments, the liquid-retaining polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.

[0019] In some embodiments, the ether polymer includes a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII),

[0020] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene;

[0021] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.

[0022] In some embodiments, the liquid-retaining polymer comprises an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.

[0023] In some embodiments, the ester polymer includes a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII),

[0024] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl;

[0025] In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.

[0026] In some embodiments, the liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.

[0027] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII),

[0028] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;

[0029] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.

[0030] In some embodiments, the molecular weight of the liquid retaining polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.

[0031] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.

[0032] In some embodiments, the isolation body includes a substrate and a heat-resistant coating, the heat-resistant coating is disposed on at least one surface of the substrate, and the polymer layer is disposed on a surface of the heat-resistant coating facing away from the substrate.

[0033] In some embodiments, the polymer layer further comprises heat-resistant particles. The heat-resistant particles and the liquid-retaining polymer act synergistically to further enhance the heat resistance and ion transmission performance of the separator as a whole.

[0034] In some embodiments, the coating weight of the polymer layer is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .

[0035] When the thickness of the polymer layer is within the above range, the heat resistance and ion transmission performance of the entire separator can be further improved.

[0036] In a second aspect, the present application proposes a battery cell comprising an isolation membrane as described in any embodiment of the first aspect of the present application.

[0037] In a third aspect, the present application proposes a battery comprising a battery cell as described in any embodiment of the second aspect of the present application.

[0038] In a fourth aspect, the present application proposes an electrical device comprising a battery as described in any embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0040] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0041] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .

[0042] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0043] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0044] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0045] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0046] The drawings are not necessarily drawn to scale.

[0047] The accompanying drawings are described as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. battery cell; 51. housing; 52. electrode assembly; 53. cover plate; 6. electrical device. DETAILED DESCRIPTION

[0048] The following detailed description specifically discloses the embodiments of the separator, battery cell, battery, and electrical device of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0049] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0052] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0053] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0054] In this application, the terms "plurality" and "multiple" refer to two or more.

[0055] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.

[0056] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.

[0057] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.

[0058] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).

[0059] A battery cell consists of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The separator is located between the positive and negative electrode sheets to isolate them from each other. During the charge and discharge cycles of a battery cell, the electrode assembly expands in volume. This expansion force is particularly high in the later stages of a battery cell cycle, increasing the distance between the electrode sheet and the separator. This increases the risk of electrode sheet electrolyte depletion and bridge failure, potentially deteriorating the battery cell's cycling performance and shortening its cycle life.

[0060] In view of the above problems, an embodiment of the present application proposes an isolation membrane, which includes a polymer layer, and the polymer layer includes an adhesive polymer and a liquid-retaining polymer; the adhesive polymer is coated on the surface of the isolation membrane to give the isolation membrane excellent adhesion, so that the electrode and the isolation membrane are tightly bonded to each other, thereby alleviating the liquid shortage caused by the increase in the gap between the electrode pieces during the battery cycle, thereby improving the cycle performance of the battery cell; on the other hand, when the liquid-retaining polymer comes into contact with the electrolyte, the polymer molecular chains stretch and open, and the electrolyte can diffuse between the molecular chains. The polymer molecular chains swell and adsorb, and a three-dimensional connection network is constructed between the isolation membrane and the electrode piece. The three-dimensional connection network can be attached to the surface of the electrode piece, bonding the isolation membrane and the electrode piece into one, further improving the stability of the electrode piece and isolation membrane structure, and improving the cycle performance of the battery cell; and the three-dimensional connection network can lock the electrolyte in the three-dimensional connection network, so that the electrolyte can be maintained in the electrode piece and diaphragm structure, which is beneficial to improving the ion transmission interface and facilitating the transmission of active ions such as lithium ions and sodium ions, and can further improve the cycle performance of the battery cell.

[0061] Isolation film

[0062] In the first aspect, an embodiment of the present application proposes an isolation membrane, which includes an isolation body and a polymer layer arranged on at least one surface of the isolation body, the polymer layer including a liquid-retaining polymer, wherein the liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; after the polymer system is allowed to stand for 8 hours at 70°C and for ≥24 hours at 25°C, the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the liquid-retaining polymer is q, and its unit is g; the mass of the first substance is m, and its unit is g; the liquid-retaining polymer and the first substance satisfy: 5≤m / q≤1000; and the bonding force of the isolation membrane is greater than or equal to 10N / m.

[0063] The isolation film has excellent adhesion, which makes the electrode and the isolation film tightly bonded to each other, thereby alleviating the liquid shortage caused by the increase in the gap between the electrodes during the battery cycle, thereby improving the cycle performance of the battery cell.

[0064] In some embodiments, 10≤m / q≤1000; further optionally, 10≤m / q≤50. For example, m / q can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of the above values.

[0065] The separator can be made from a substrate and a liquid-retaining polymer. Alternatively, the separator is derived from a battery cell. The battery cell is disassembled, and the separator soaked in the electrolyte is removed from the battery cell. The separator is then rinsed with deionized water and vacuum-dried at 80°C for 12 hours to obtain the separator, which is then used for separator testing.

[0066] The polymer system is allowed to stand at 70°C for 8 hours and at 25°C for ≥24 hours. After undergoing two stages of standing treatment, part of the polymer system is transformed into a gel-state substance through swelling and adsorption; the liquid-retaining polymer contacts the electrolyte, the polymer molecular chains stretch and open, the electrolyte can diffuse between the molecular chains, the polymer molecular chains swell and adsorb, and a three-dimensional connection network is constructed between the isolation membrane and the electrode. The three-dimensional connection network can adhere to the surface of the electrode, bonding the isolation membrane and the electrode into one, further improving the stability of the electrode and isolation membrane structure, thereby improving the cycle performance of the battery cell; and the three-dimensional connection network can lock the electrolyte in the three-dimensional connection network, so that the electrolyte can be maintained in the electrode and diaphragm structure, which is beneficial to improving the ion transmission interface and the transmission of active ions such as lithium ions and sodium ions, and can further improve the cycle performance of the battery cell.

[0067] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the liquid-retaining polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.

[0068] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include at least one of a carbonate solvent and an ether solvent. For example, the carbonate solvent includes a cyclic carbonate solvent and / or a linear carbonate solvent.

[0069] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.

[0070] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.

[0071] As examples of the ether solvent, the ether solvent includes one or more of tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diglyme DG.

[0072] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.

[0073] In this application, m / q is also referred to as the precipitation value, which characterizes the ability of the liquid-retaining polymer and the solvent to transform into a gel-state substance.

[0074] The first substance mainly includes a gel-state substance formed by a liquid-retaining polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.

[0075] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry (IR) or nuclear magnetic resonance (NMR) testing shows that the main component of the first substance after drying is the liquid-retaining polymer described above.

[0076] By increasing the temperature, embodiments of the present application can achieve stretching of the liquid-retaining polymer molecular chains within the safe operating temperature range of the battery cell, promoting mutual attraction and physical bonding between the polymer molecular chains and the electrolyte. At room temperature, the activity of the liquid-retaining polymer molecular segments decreases, allowing them to remain attached to the surface of the isolation body and lock the electrolyte within the space surrounding the liquid-retaining polymer, forming a gel or gel-like state. This can increase the transport rate of active ions, such as lithium ions, and improve cycling performance.

[0077] In some embodiments, the bonding force of the separator is greater than or equal to 10 N / m; it can be optionally 10 N / m to 30 N / m. When the bonding force of the separator is within the above range, the separator has good bonding properties, which is beneficial to improving the connection stability between the separator and the pole piece. During the charge and discharge cycle of the battery cell, the risk of increasing the distance between the separator and the pole piece is reduced, thereby enabling the electrode assembly to adsorb more electrolyte, which is beneficial to improving the cycle performance. Exemplarily, the bonding force of the separator is 10 N / m, 12 N / m, 15 N / m, 16 N / m, 18 N / m, 20 N / m, 22 N / m, 25 N / m, 28 N / m, 30 N / m or a range consisting of any two of the above values. The bonding force of the separator mainly refers to the bonding force on the side with the polymer layer.

[0078] In the embodiment of the present application, the adhesion of the isolation membrane is tested using equipment and methods known in the art. For example, the positive electrode sheet, the isolation membrane and the negative electrode sheet are stacked in sequence to form a laminated electrode assembly, and the electrode assembly is placed in a hot pressing machine, hot pressed at 80°C and a pressure of 8000N for 120s, and then placed in a high-speed rail tensile testing machine. The adhesion shown in the high-speed rail tensile testing machine is the adhesion of the isolation membrane.

[0079] In some embodiments, the polymer layer can be formed by spraying a mixed system consisting of a liquid-retaining polymer and a solvent onto the isolation body. The solvent can include at least one of an aqueous solvent and an oily solvent. The oily solvent can be understood as an organic solvent.

[0080] When the solvent includes an aqueous solvent such as water, an adhesive polymer may be added to the mixed system to improve the bonding ability of the polymer layer. In some embodiments, the adhesive polymer may include one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and polyethyl acetate (VAE emulsion). These adhesive polymers have good bonding properties. Optionally, the polyacrylate includes ethyl acrylate.

[0081] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer is (1 to 9):1. When the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer is within this range, both the adhesion and gel properties of the polymer layer can be improved. For example, the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer can be 1:1, 2:1, 3:1, 5:1, 6:1, 7:1, 8:1, 9:1, or a range consisting of any two of these values.

[0082] The particle size of the liquid-retaining polymer may be smaller than that of the adhesive polymer. The polymer layer can be considered to be composed of large particles of adhesive polymer with high adhesion and small particles of liquid-retaining polymer. The large particles agglomerate to form protrusions, and the polymer layer presents an island structure.

[0083] In the case where the solvent includes an oily solvent such as N-methylpyrrolidone NMP and / or polyethersulfone, the polymer layer can include an oily solvent and a liquid-retaining polymer, and the liquid-retaining polymer can exert adhesive properties, so that the isolation film has excellent adhesive properties, and the formed polymer layer presents a network structure.

[0084] When the polymer layer and the electrolyte are in contact, the molecular chain segments of the liquid-retaining polymer are stretched and the electrolyte is adsorbed in the chain segments, forming a three-dimensional cross-linked network structure between the electrode and the electrode, which allows the active ions to be quickly transferred at the interface between the electrolyte and the electrode. In addition, due to the introduction of highly adhesive polymers in the three-dimensional cross-linked network structure, the separator and the electrode can be tightly bonded, reducing the problem of increased distance between the electrode and the separator caused by the expansion of the electrode in the later stage of the cycle. The electrolyte can be continuously transferred and the electrolyte can be transferred along the initial state path, reducing the risk of electrolyte bridge breakage caused by expansion during the cycle. The electrode interface is less prone to risks such as lithium deposition, thereby improving the cycle performance of the battery cell.

[0085] The polymer layer in the embodiment of the present application can be prepared by the following steps:

[0086] adding a liquid-retaining polymer and an optional adhesive polymer into a solvent to form a mixed system;

[0087] The mixed system is atomized and sprayed onto the surface of the isolation body to form a polymer layer.

[0088] When sprayed with an aqueous solvent atomization method, the adhesive polymer can provide excellent adhesion to the separator, and the polymer layer may appear as an island structure.

[0089] When oily solvent atomization spraying is used, the liquid-retaining polymer has a certain adhesive ability, the adhesive polymer can further increase the adhesive ability, and the polymer layer may present a network structure.

[0090] In some embodiments, the coating weight of the polymer layer is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .

[0091] When the coating weight is within the above range, the ability to form a gel-like substance with the electrolyte can be further improved, thereby increasing the liquid absorption rate. Optionally, the coating weight of the polymer layer of the isolation film is 0.5 mg / 1540.25 mm 2 Up to 3.5mg / 1540.25mm 2 .

[0092] For example, the coating weight of the polymer layer of the isolation film can be 0.5 mg / 1540.25 mm 2 、0.8mg / 1540.25mm 2 、1.0mg / 1540.25mm 2 、1.2mg / 1540.25mm 2 、1.3mg / 1540.25mm 2 、1.5mg / 1540.25mm 2 , 2.0mg / 1540.25mm 2 , 2.2mg / 1540.25mm 2 , 2.5mg / 1540.25mm 2 、3mg / 1540.25mm 2 、3.5mg / 1540.25mm 2 、4mg / 1540.25mm 2 4.5mg / 1540.25mm 2、5mg / 1540.25mm 2 Or a range consisting of any two of the above values.

[0093] In the embodiment of the present application, the coating weight refers to the coating weight of the polymer layer on one side of the isolation film, which can be detected by using equipment and methods known in the art, for example, by cutting the same mother roll substrate and isolation film into 1540.25mm 2 The weight of 10 small discs of the isolation film is respectively weighed, and the coating weight of the polymer layer in the isolation film can be obtained by calculation.

[0094] In some embodiments, the liquid retaining polymer may include one or more of a fluorinated polymer, an ether polymer, an ester polymer, and a ketone-aldehyde polymer.

[0095] In some embodiments, the liquid-retaining polymer comprises a fluorinated polymer having a crystallinity of X 0. C1 ,0<X C1 ≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.

[0096] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. The intermolecular force will affect the packing density between molecular chains. C1 It is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature rise and fall treatment on the sample under a nitrogen atmosphere, with a heating rate of 10℃ / min from the intrinsic T g1 The initial temperature is 20℃ lower and then heated to the intrinsic T m1 The cut-off temperature of the process is 20℃ higher. The actual glass transition temperature T of the material is determined according to the endothermic and exothermic peak or transition point of the material in the process. g1 and melting temperature T m1 wait.

[0097] As a result, fluoropolymers have relatively low crystallinity and melting temperature, which makes the molecular chains tend to be loose, the interaction force between the molecular chains is small, adjacent molecular chains are easily opened, and the chain segment movement is achieved through intermolecular rotation, forming a molecular chain structure with high flexibility; and the fluoropolymers and the electrolyte in the battery cell can form a gel-like substance, thereby improving the cycle performance of the battery cell.

[0098] For example, the crystallinity X of the fluorinated polymer measured by differential scanning calorimetry isC1 It can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.

[0099] For example, the melting temperature of the fluorinated polymer may be 10° C., 20° C., 50° C., 70° C., 90° C., 100° C., 120° C., 140° C., or a range consisting of any two of the foregoing values.

[0100] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.

[0101] The glass transition temperature is the temperature at which the chain segments of a polymer transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The lower the glass transition temperature of a polymer, the better the segment flexibility of the molecular chain, and the easier it is for adjacent molecular chains to be opened. For example, the glass transition temperature of a fluorinated polymer can be -150°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.

[0102] In some embodiments, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),

[0103] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom.

[0104] In formula (AIII), R 15 This includes single bonds, substituted or unsubstituted C1-C3 alkyl groups.

[0105] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. The above-mentioned substituents are high-pressure resistant substituents, which are more conducive to stabilizing the structure of the polymer. The halogen atom may include a fluorine atom, a chlorine atom, a bromine atom, etc. Alternatively, the halogen atom includes a fluorine atom.

[0106] In the embodiments of the present application, the polymer may also be obtained by copolymerizing the above structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers, etc.).

[0107] In some embodiments, p is a positive integer selected from 1 to 3.

[0108] In some embodiments, n is a positive integer selected from 1,000 to 30,000.

[0109] In some embodiments, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.

[0110] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AI-1) to the structural units represented by formula (AI-11),

[0111] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AII-1) to the structural units represented by formula (AII-5),

[0112] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AIII-1) to the structural units represented by formula (AIII-3),

[0113] Illustratively, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).

[0114] Optionally, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).

[0115] The fluoropolymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene. Alternatively, the fluoropolymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene.

[0116] The monomers used in the above-mentioned fluorinated polymers are all short-chain monomers, which are conducive to polymerization to form straight-chain linear structures or short-chain branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby facilitating the formation of a three-dimensional gel-like substance between the polymer and the electrolyte, which is conducive to further improving the liquid absorption rate.

[0117] In some embodiments, n is a positive integer selected from 5,000 to 20,000.

[0118] In some embodiments, the molecular weight of the liquid retaining polymer is 1.2×10 5 g / mol to 1.5×10 6 g / mol; optional: 1.2×10 5 g / mol to 1.0×10 6When the polymer molecular weight is within the above range, it can ensure a certain solubility of the polymer in the electrolyte while being difficult to be completely dissolved and dispersed by the electrolyte, which is conducive to regulating the distribution and dispersion of the polymer. It can also further improve the flexibility between the polymer molecular chains. The interaction between the molecular chains is relatively weak, which facilitates the solvent molecules in the electrolyte to open the molecular chains, enter between the molecular chains, and be wrapped by the molecular chains. This facilitates the entry of active ions into the active material through the solvent, achieving smooth and rapid migration of active ions.

[0119] When the molecular weight of the liquid-retaining polymer is within the above range, it can ensure that the polymer exhibits a certain solubility in the electrolyte, while not being easily completely dissolved and dispersed by the electrolyte, which is beneficial for regulating the distribution and dispersion of the polymer on the surface of the active material; and it can further improve the flexibility between the molecular chains of the polymer. The interaction force between the molecular chains is relatively weak, which is beneficial for the solvent molecules in the electrolyte to open the molecular chains and enter between the molecular chains and be wrapped by the molecular chains. This is beneficial for the active ions to enter the active material through the solvent, realizing the smooth and rapid migration of the active ions. For example, the molecular weight of the polymer can be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.

[0120] [Ether polymers]

[0121] In some embodiments, the liquid-retaining polymer includes an ether polymer, and the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 °C represents the melting temperature of the ether polymer.

[0122] Specifically, the sheet structure is prepared as follows: the ether polymer is vacuum dried at 80°C for 12 hours. The dried ether polymer is hot-pressed into a sheet by a flat vulcanizer, and the hot-pressing temperature is set to (T m2The sample is then removed from the press after 2 minutes of calendering and placed on another vulcanizing press of the same model for cold pressing at a pressure of 10 MPa. A polymer disc (sheet structure) of fixed size is obtained using a circular mold with a diameter of 25 mm. For example, the sheet structure can be a disc with a thickness of 1-2 mm and a diameter of 25 mm; alternatively, a sample can be prepared according to the sample standard required by the test equipment.

[0123] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.

[0124] The specific steps of the dynamic frequency sweep test are as follows: The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA) with a parallel plate diameter of 25 mm and a thickness of 0.9 mm. To ensure that the test was in the linear point-bounce region, the strain during the dynamic frequency sweep test was 2% and the test temperature was T m2 +20℃, test frequency sweep range: 500rad / s≤w 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.

[0125] The dynamic frequency sweep test can characterize the degree of entanglement of molecular chains under solid-phase melting (melt state). Compared with linear structures or short-chain branched structures, long-branched structures, network structures, and low-crosslinked structures have a high degree of entanglement, which will show deviation from linear terminal behavior. Ether polymers exhibit solid-phase behavior. When the ether polymers of the present application meet the above range, the entanglement state of the molecular chains can be further reduced, which is conducive to the diffusion of solvent molecules in the electrolyte between the molecular chains; moreover, the ether polymers still maintain a certain degree of molecular chain entanglement and can form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.

[0126] In some embodiments, 1<K1≤100; alternatively, 1<K1≤10. For example, K1 can be 1.01, 1.1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.

[0127] In some embodiments, the glass transition temperature of the ether polymer is T g2 , its unit is ℃, -100≤T g2 ≤50; optionally, -80≤T g2≤30. For example, the glass transition temperature of the ether polymer may be -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.

[0128] In some embodiments, the ether polymer includes a structural unit represented by formula (BI),

[0129] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 This includes substituted or unsubstituted C1-C5 methylene groups.

[0130] In some embodiments, R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group.

[0131] In some embodiments, R 23 It includes single bonds, substituted or unsubstituted C1-C4 methylene groups.

[0132] Illustratively, the ether polymer includes at least one of the structural units represented by formula (BI-1) to the structural units represented by formula (BI-8),

[0133] In some embodiments, the ether polymer comprises a structural unit represented by formula (BII),

[0134] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.

[0135] In some embodiments, R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group, a substituted or unsubstituted C1-C2 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C2 alkoxy group or an ether group.

[0136] In some embodiments, the ether polymer includes at least one of the structural units represented by formula (BII-1) to the structural units represented by formula (BII-7),

[0137] The monomers used in the above-mentioned ether polymers are polycyclic rings, such as structures with six or less members, or short-chain monomers, which are conducive to the polymerization to form a high-content -O- structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery monomer.

[0138] The above-mentioned polymers are only examples of the structural groups of the main molecular chains. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).

[0139] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.

[0140] In some embodiments, n is a positive integer selected from 1,500 to 25,000.

[0141] Optionally, n is a positive integer selected from 3000 to 18000.

[0142] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.

[0143] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.

[0144] [Ester polymer]

[0145] In some embodiments, the liquid-retaining polymer comprises an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 °C represents the melting temperature of the ester polymer.

[0146] When the ester polymer of the embodiment of the present application meets the above range, the entanglement state of the molecular chains can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between the molecular chains; and the ether polymer still maintains a certain molecular chain entanglement state, can form a gel-like substance with the electrolyte, can increase the liquid absorption rate, and thereby improve the cycle performance and storage performance of the battery cell.

[0147] In some embodiments, 1<K2≤100; optionally, 1<K2≤10.

[0148] Illustratively, K2 may be 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.

[0149] In some embodiments, the glass transition temperature of the ester polymer is T g3 , its unit is ℃, -100≤T g3 ≤50; optionally, -80≤T g3 ≤30.

[0150] For example, the glass transition temperature of the ester polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.

[0151] In some embodiments, the ester polymer comprises a structural unit represented by formula (CI),

[0152] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; optionally, R 34 It includes substituted or unsubstituted C1-C6 alkyl groups, or substituted or unsubstituted C1-C6 hydroxyalkyl groups.

[0153] Optionally, R 31 This includes a hydrogen atom, or a substituted or unsubstituted methyl group.

[0154] Optionally, R 32 and R 33 Each independently includes a hydrogen atom.

[0155] Optionally, R 34 It includes substituted or unsubstituted C1-C4 alkyl groups, or substituted or unsubstituted C1-C4 hydroxyalkyl groups.

[0156] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CI-1) to the structural units represented by formula (CI-15),

[0157] In some embodiments, the ester polymer comprises a structural unit represented by formula (CII),

[0158] In formula (CII), R 35 This includes substituted or unsubstituted C2-C6 methylene groups.

[0159] Optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.

[0160] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CII-1) to the structural units represented by formula (CII-5),

[0161] The molecular chains of the above-mentioned ester polymers have a low degree of entanglement, which is conducive to improving the flexibility of the molecular chains. The molecular chains can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte.

[0162] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, acrylonitrile structural units, maleic anhydride and other monomers with functional groups).

[0163] When the above groups are substituted, the substituents may include one or more of a nitrile group, a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. The above substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer.

[0164] In some embodiments, n is a positive integer selected from 800 to 20,000.

[0165] Optionally, n is a positive integer selected from 1000 to 15000.

[0166] In some embodiments, the molecular weight of the polymer is 1.2×10 5g / mol to 1.0×10 6 g / mol.

[0167] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.

[0168] [Ketone-aldehyde polymers]

[0169] In some embodiments, the liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 °C represents the melting temperature of the aldehyde-ketone polymer.

[0170] In some embodiments, 0.8≤K3≤100; optionally, 0.8≤K3≤10.

[0171] Illustratively, K3 may be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.

[0172] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is T g4 , its unit is ℃, -100≤T g4 ≤50; optionally, -80≤T g4 ≤30.

[0173] For example, the glass transition temperature of the aldehyde-ketone polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.

[0174] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI),

[0175] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;

[0176] Optionally, R 41 including single bonds, substituted or unsubstituted C1-C2 methylene groups;

[0177] Optionally, R 42 This includes hydrogen atoms, and substituted or unsubstituted C1-C3 alkyl groups.

[0178] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond, for example, R 41 is a single bond, indicating R 41 The carbon atoms on both sides are connected by single bonds.

[0179] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DI-1) to the structural units represented by formula (DI-6),

[0180] Illustratively, the aldehyde-ketone polymer includes a structural unit represented by formula (DII),

[0181] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer; optionally, R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.

[0182] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DII-1) to the structural units represented by formula (DII-4),

[0183] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, which is conducive to forming a gel-state substance with the electrolyte.

[0184] The above polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, enol structural units, acrylonitrile structural units, etc.).

[0185] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. These substituents are high-pressure-resistant substituents and are more conducive to stabilizing the structure of the polymer.

[0186] In some embodiments, n is a positive integer selected from 500 to 15,000.

[0187] Optionally, n is selected from a positive integer between 500 and 10,000.

[0188] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.

[0189] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.

[0190] The relevant parameters of the liquid-retaining polymer according to the embodiment of the present application can be detected by the following methods:

[0191] The groups of the liquid-retaining polymer of the embodiment of the present application can be detected by infrared spectrophotometry IR. Specifically, the liquid-retaining polymer is tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.

[0192] The structure of the liquid-retaining polymer according to the embodiment of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.

[0193] The polymer monomer type of the liquid-retaining polymer in the embodiment of the present application (especially suitable for monomers that account for a relatively small proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific testing steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) injection port. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by a flame ionization detector FID or a mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.

[0194] The molecular weight of the liquid-retaining polymer in the embodiment of the present application is well known in the art and can be measured using commonly used equipment and methods in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously ultraviolet (53KHz / 120W) for 5 minutes to ensure that the sample is completely dispersed. Then, the sample is measured in accordance with the GB / T19077-2016 / ISO 13320:2009 standard.

[0195] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.

[0196] In an embodiment of the present application, the isolation membrane includes an isolation body and a polymer layer. The polymer layer is disposed on at least one surface of the isolation body, meaning that the polymer layer can be disposed on one surface of the isolation body or on both surfaces of the isolation body. Since the isolation body has various structural forms, the polymer layer can be disposed in various configurations accordingly. The liquid-retaining polymer can be dispersed in a solvent to form a polymer mixture system, and the polymer mixture system can be applied to the isolation body via a coating process such as atomization spraying or gravure coating.

[0197] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.

[0198] In other embodiments, the isolation body includes a substrate and a heat-resistant coating, wherein the heat-resistant coating is disposed on at least one surface of the substrate, and the polymer layer is disposed on the surface of the heat-resistant coating facing away from the substrate. It will be understood that the heat-resistant coating can be disposed on one surface of the substrate, or on both surfaces of the substrate.

[0199] The embodiments of the present application are not particularly limited to the material of the substrate. Any known substrate with good chemical and mechanical stability can be selected. For example, the substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different.

[0200] In some embodiments, the porosity of the substrate is greater than or equal to 25%, and can be optionally between 25% and 50%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be improved, which is beneficial for the migration of active ions. Moreover, due to the relatively small porosity, the mechanical properties of the substrate can be improved, and it can provide good support for the polymer layer.

[0201] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 5 μm to 12 μm. For example, the thickness of the substrate may be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.

[0202] The heat-resistant coating may include heat-resistant particles. In some embodiments, the heat-resistant particles include at least one of inorganic particles and organic particles. By adding heat-resistant particles, the heat resistance of the isolation film can be improved.

[0203] In some embodiments, the mass percentage of the inorganic particles in the heat-resistant coating is ≤ 30. For example, the mass percentage of the inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range consisting of any two of the above values.

[0204] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.

[0205] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).

[0206] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).

[0207] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with olivine structures, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.

[0208] In some embodiments, the heat-resistant coating may also include other organic particles, for example, the organic particles may include polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate and mixtures thereof.

[0209] In some embodiments, the heat-resistant coating may further include a binder. For example, the binder may include at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate monomers, or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.

[0210] In some embodiments, the thickness of the heat-resistant coating may be ≤4 μm. This helps to improve the energy density of the battery cell. In the embodiments of the present application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on a single side of the substrate. For example, the thickness of the heat-resistant coating may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.

[0211] In some embodiments, the polymer layer may also include heat-resistant particles. The heat-resistant particles and the liquid-retaining polymer work synergistically to further enhance the overall heat resistance and ion transport properties of the separator. The liquid-retaining polymer and heat-resistant particles can be dispersed in a solvent to form a polymer mixture, which is then applied to the separator body via a coating process such as atomization spraying or gravure coating.

[0212] In some embodiments, the thickness of the polymer layer may be 0.5 μm to 3.0 μm; optionally, 1.0 μm to 2.0 μm. When the thickness of the polymer layer is within the above range, the heat resistance and ion transmission performance of the isolation membrane as a whole can be further improved. For example, the thickness of the polymer layer may be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm, or a range consisting of any two of the above values.

[0213] battery cells

[0214] In the second aspect, an embodiment of the present application proposes a battery cell, which includes an electrode assembly and an electrolyte, the electrode assembly includes a positive electrode sheet, a negative electrode sheet and an isolation membrane, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the isolation membrane includes an isolation membrane as in any embodiment of the first aspect of the present application.

[0215] [Positive electrode]

[0216] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.

[0217] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.

[0218] The positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in battery cells. For example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate compound, a lithium-containing transition metal oxide, a sodium-containing phosphate compound, and a sodium-containing transition metal oxide.

[0219] For example, the general formula of the olivine-type phosphate active material (lithium-containing phosphate compound) is: Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0220] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich layered and rock salt phase layered materials). The general formula of the layered structure positive electrode active material is: Li x Ay Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.

[0221] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0222] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.

[0223] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The embodiments of the present application do not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the fluoropolymer of the embodiment of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the fluoropolymer of the embodiment of the present application, the melting temperature of the positive electrode binder is higher.

[0224] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP). Of course, the preparation of the positive electrode sheet is not limited to the above method; the preparation methods described above can also be used.

[0225] [Negative electrode]

[0226] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material.

[0227] Illustratively, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.

[0228] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.

[0229] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode conductive agent. The present embodiments do not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.

[0230] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode active material layer is ≤5%.

[0231] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode active material layer.

[0232] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0233] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation methods described above may also be used.

[0234] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.

[0235] [Electrolytes]

[0236] During the charge and discharge process of a battery cell, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it can be selected according to actual needs.

[0237] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.

[0238] When the battery cell of the present application is a lithium-ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0239] When the battery cell of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0240] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0241] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0242] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.

[0243] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0244] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0245] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.

[0246] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.

[0247] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0248] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.

[0249] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.

[0250] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0251] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0252] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0253] Both the battery module 4 and the battery pack can be used as specific examples of batteries in the embodiments of the present application.

[0254] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0255] Electrical devices

[0256] In a third aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0257] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.

[0258] Example

[0259] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0260] Example 1 Preparation of lithium-ion battery

[0261] (1) Preparation of positive electrode sheet:

[0262] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0263] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of N-methylpyrrolidone (NMP) to create a positive electrode slurry. The mass ratio of NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 97.5:1.4:1. The positive electrode slurry is coated on a current collector aluminum foil and vacuum-dried at 100°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried at 85°C under vacuum for 4 hours to form the positive electrode sheet.

[0264] (2) Preparation of negative electrode sheet:

[0265] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0266] The negative electrode active material (artificial graphite), conductive agent (carbon black), binder (styrene-butadiene rubber (SBR), and thickener (sodium carboxymethyl cellulose (CMC)) were mixed uniformly in a weight ratio of 97.4:2:0.5:0.1 and added to deionized water to form the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.

[0267] (3) Preparation of electrolyte:

[0268] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then the lithium salt LiPF6 is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0269] (4) Preparation of isolation membrane

[0270] A 7 μm polyethylene film (PE) was used as the substrate.

[0271] A binder polymer (polyethyl acrylate) and a liquid-retaining polymer are dispersed in a dimethyl carbonate (DMC) solvent to form a mixed system. The mixed system is then atomized and sprayed onto both surfaces of a polyethylene film to form polymer layers. Water is used as the atomizing solvent, and the weight content of the binder polymer (polyethyl acrylate) and liquid-retaining polymer in the mixed system is 1%.

[0272] (5) Preparation of lithium-ion batteries:

[0273] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0274] Comparative Example 1

[0275] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the separator in Comparative Example 1 was a polyethylene film (PE) with a thickness of 7 μm.

[0276] Comparative Example 2

[0277] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the liquid-retaining polymer of the isolation membrane in Comparative Example 2 was changed.

[0278] Example 1-2 to Example 1-5

[0279] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 was that the amount of adhesive polymer added to the polymer layer of the separator in Examples 1-2 to 1-6 was adjusted.

[0280] Example 2-1 to Example 2-3

[0281] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the type of liquid-retaining polymer in the polymer layer of the separator in Examples 2-1 and 2-3 was adjusted.

[0282] Example 3-1 to Example 3-5

[0283] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the coating weights of the isolation films in Examples 3-1 to 3-5 were adjusted.

[0284] Example 4-1

[0285] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Example 4-1 adjusted the position of the polymer layer of the separator. Specifically, the steps of preparing the separator included:

[0286] 7μm polyethylene film (PE) was used as the separator substrate;

[0287] The silicon oxide particles and the adhesive polymer aqueous solution type polyacrylic acid are uniformly mixed in an appropriate amount of solvent deionized water at a mass ratio of 20:80 to obtain a coating slurry.

[0288] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.

[0289] The liquid-retaining polymer and the adhesive polymer are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is atomized and sprayed on the surface of the heat-resistant coating to form a polymer layer, thereby obtaining a separator.

[0290] The data of the examples and comparative examples are shown in Table 1.

[0291] Test section

[0292] 1. Lithium-ion battery performance test (25min fast charge cycle performance)

[0293] At 25°C, the lithium-ion battery was charged at a 3C rate and discharged at a 1C rate for a full charge-discharge cycle test until the capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.

[0294] 2. Adhesion test of isolation film

[0295] The positive and negative electrode sheets and the isolation film are stacked into a laminate with a structure of one negative electrode sheet, one isolation film and one positive electrode sheet; the device containing the electrode sheets and the isolation film is placed in a hot pressing machine and hot pressed at 80°C and a pressure of 8000N for 120S.

[0296] The hot-pressed electrode and isolation membrane are placed in a high-speed rail tensile testing machine, and the adhesion strength between the electrode and the isolation membrane displayed by the high-speed rail tensile testing machine is expressed as the adhesion strength of the isolation membrane.

[0297] Test results

[0298] The test results are shown in Table 1.

[0299] Table 1

[0300] In Table 1, 88% vinyl ethyl ether means that the molar percentage of vinyl ethyl ether is 88% based on the total molar amount of vinyl ethyl ether and vinyl acetate. The liquid retaining polymer in Example 2-1 has a crystallinity of 10% and a melting temperature of 110°C.

[0301] Compared with Comparative Example 1, the embodiment of the present application adds the liquid-retaining polymer of the present application to the isolation membrane, and the cycle performance of the lithium-ion battery is improved. Compared with Comparative Example 1, the embodiment of the present application is provided with a polymer layer on the surface of the isolation membrane. The polymer layer is in contact with the electrolyte, the polymer molecular chains stretch and open, and the electrolyte can diffuse between the molecular chains, forming a three-dimensionally connected interface between the isolation membrane and the electrode. The introduction of the liquid-retaining polymer can form a uniform high wetting point between the isolation membrane and the electrode, uniformly improve the wetting performance of the isolation membrane and the electrode, thereby improving the liquid absorption rate of the isolation membrane and the electrode, thereby improving the cycle performance of the battery cell; further introducing an adhesive polymer into the polymer layer can further improve the bonding ability of the interface, so that the isolation membrane and the electrode have high adhesion, and the connection between the two is more stable, thereby alleviating the expansion of the electrode assembly to a certain extent, and further improving the cycle performance of the battery cell.

[0302] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.

Claims

1. A separation film, comprising: Isolate the body; a polymer layer disposed on at least one surface of the isolation body, the polymer layer comprising a liquid-retaining polymer, in, The liquid retaining polymer is added to the first solvent at 70° C. to form a polymer system; The polymer system is allowed to stand at 70° C. for 8 hours and at 25° C. for ≥24 hours, and the polymer system is filtered through a 200-mesh filter to leave the first substance. in, The mass of the liquid-retaining polymer is q, and its unit is g; The mass of the first substance is m, and its unit is g; The liquid retaining polymer and the first substance satisfy: 5≤m / q≤1000; The adhesive force of the isolation film is greater than or equal to 10 N / m.

2. The isolation film according to claim 1, wherein: The isolation film has an adhesive force of 10 N / m to 30 N / m.

3. The isolation film according to claim 1 or 2, wherein: The polymer layer includes an adhesive polymer, and the adhesive polymer includes one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and polyethyl acetate (VAE emulsion); Optionally, based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer is (1 to 9):

1.

4. The separator according to any one of claims 1 to 3, wherein: The liquid retaining polymer comprises a fluorinated polymer; The crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; The melting temperature of the fluorinated polymer is T m1 , its unit is ℃, 0<T m1 ≤140.

5. The battery cell according to claim 4, wherein: The glass transition temperature of the fluorinated polymer is T g1 , the unit is ℃, -150≤T g1 ≤60.

6. The battery cell according to claim 4 or 5, wherein: The fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII), In formula (AI) and formula (AII), R 11 , R 12 , R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 , R 12 , R 13 and R 14 At least one of them contains a fluorine atom; In formula (AIII), R 15 Including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is selected from a positive integer from 1 to 3; n is selected from a positive integer from 1000 to 30000.

7. The battery cell according to any one of claims 1 to 6, wherein: The liquid-retaining polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet-like structure; the sheet-like structure is m2 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at +20)℃, and the slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.

8. The battery cell according to claim 7, wherein: The ether polymer comprises a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII), In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene; In formula (BII), R 24 To R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.

9. The battery cell according to any one of claims 1 to 8, wherein: The liquid-retaining polymer comprises an ester polymer, wherein the ester polymer is made into a sheet-like structure; the sheet-like structure is m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency scanning test at 20 °C. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.

10. The battery cell according to claim 9, wherein: The ester polymer comprises a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII), In formula (CI), R 31 , R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.

11. The battery cell according to any one of claims 1 to 10, wherein: The liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet-like structure; the sheet-like structure is m4 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at 20 ° C. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.

12. The battery cell according to claim 11, wherein: The aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII), In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 Including hydrogen atom, substituted or unsubstituted C1-C6 alkyl; In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.

13. The battery cell according to any one of claims 1 to 12, wherein: The molecular weight of the liquid-retaining polymer is 1.2×10 5 g / mol to 1×10 6 g / mol.

14. The separator according to any one of claims 1 to 13, wherein: The isolation body comprises a substrate, and the polymer layer is disposed on at least one surface of the substrate.

15. The separator according to any one of claims 1 to 13, wherein: The isolation body comprises a substrate and a heat-resistant coating, wherein the heat-resistant coating is arranged on at least one surface of the substrate, and the polymer layer is arranged on the surface of the heat-resistant coating facing away from the substrate.

16. The separator according to any one of claims 1 to 15, wherein: The coating weight of the polymer layer is 0.5 mg / 1540.25 mm2 to 5 mg / 1540.25 mm 2 . 17 . A battery cell comprising the separator according to claim 1 .

18. A battery comprising the battery cell according to claim 17.

19. An electrical device comprising the battery according to claim 18.

Citation Information

Patent Citations

  • Preparation method of high-adhesion coating diaphragm and prepared coating diaphragm

    CN110690390A

  • Polymer coating diaphragm with improved structure and preparation method thereof

    CN110993859A

  • Solid electrolyte secondary battery and its manufacturing method

    JP2002008726A

  • High performance, temperature resistant, printable separator

    US20160365557A1

  • Ion polymer membrane material, preparation process therefor and lithium secondary battery

    WO2013181967A1